Determining isoleucine side-chain rotamer-sampling in proteins from (13)C chemical shift - Siemons, Lucas (Royal Society of Chemistry, 2019)

(untitled) (Chem Commun (Camb))
Chemical shifts are often the only nuclear magnetic resonance parameter that can be obtained for challenging macromolecular systems. Here we present a framework to derive the conformational sampling of isoleucine side chains from (13)C chemical shifts and demonstrate that side-chain conformations in a low-populated folding intermediate can be determined.